A comprehensive review of highly pathogenic avian influenza (HPAI) H5N1: An imminent threat at doorstep - Javad Charostad; Mohammad Rezaei Zadeh Rukerd; Shahab Mahmoudvand; Davood Bashash; Seyed Mohammad Ali Hashemi; Mohsen Nakhaie; Keivan Zandi (Travel Medicine and Infectious Disease, 2023)
Avian influenza viruses (AIVs) are globally challenging due to widespread circulation and high mortality rates. Highly pathogenic avian influenza (HPAI) strains like H5N1 have caused significant outbreaks in birds. Since 2003 to 14 July 2023, the World Health Organization (WHO) has documented 878 cases of HPAI H5N1 infection in humans and 458 (52.16%) fatalities in 23 countries. Recent outbreaks in wild birds, domestic birds, sea lions, minks, and etc., and the occurrence of genetic variations among HPAI H5N1 strains raise concerns about potential transmission and public health risks. This paper aims to provide a comprehensive overview of the current understanding and new insights into HPAI H5N1. It begins with an introduction to the significance of studying this virus and highlighting the need for updated knowledge. The origin and evaluation of HPAI H5N1 are examined, shedding light on its emergence, and spread across different geographic regions. The genome organization and structural biology of the H5N1 virus are explored, providing insights into its molecular composition and key structural features. This manuscript also delves into the phylogeny, evolution, mutational trends, reservoirs, and transmission routes of HPAI H5N1. The immune response against HPAI H5N1 and its implications for vaccine development are analyzed, along with an exploration of the pathogenesis and clinical manifestations of HPAI H5N1 in human cases. Furthermore, diagnostic tools and preventive and therapeutic strategies are discussed, highlighting the current approaches and potential future directions for better management of the potential pandemic.